2003
DOI: 10.1021/jp030242w
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Studies of Acid−Base Equilibria of Substituted 4-NitropyridineN-Oxides

Abstract: By using the potentiometric titration method, acidity constants in the polar aprotic solvent acetonitrile (in the form of pK a AN values) of cations obtained by protonation of 13 substituted 4-nitropyridine N-oxides and cationic homoconjugation constants (K BHB + ) of the cationic acids conjugated with the N-oxides studied have been determined. A correlation has been established between the tendency toward cationic homoconjugation (expressed as log K BHB + ) and the basicity of the N-oxides in acetonitrile (pK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…From the large class of the methyl derivatives of 4-nitropyridine-N-oxide only one compound, that with one methyl group positioned at C(3) interacts with copper(II) acetate Scheme 2 The ligand field splitting patterns for d 9 configuration in D 4h , D 4h distorted and C 4v symmetries (graphically presented according to Boudreaux data [42]) Table 5 The reflectance spectra in the range 20,000-45,000 cm -1 for [Cu(OAc) 2 (3-mnpn)] 2 with the isolation of a solid, crystalline product. The reaction results in the formation of the dinuclear [Cu(OAc) 2 (L)] 2 complex with atypically short Cu-Cu bond, which was confirmed by preliminary X-ray diffraction studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the large class of the methyl derivatives of 4-nitropyridine-N-oxide only one compound, that with one methyl group positioned at C(3) interacts with copper(II) acetate Scheme 2 The ligand field splitting patterns for d 9 configuration in D 4h , D 4h distorted and C 4v symmetries (graphically presented according to Boudreaux data [42]) Table 5 The reflectance spectra in the range 20,000-45,000 cm -1 for [Cu(OAc) 2 (3-mnpn)] 2 with the isolation of a solid, crystalline product. The reaction results in the formation of the dinuclear [Cu(OAc) 2 (L)] 2 complex with atypically short Cu-Cu bond, which was confirmed by preliminary X-ray diffraction studies.…”
Section: Discussionmentioning
confidence: 99%
“…Substituted pyridine N-oxides (mnpn) are an interesting group of compounds applied as catalysts [1][2][3][4][5], reactive intermediates and drugs in pharmaceutical chemistry [6][7][8][9]. Recently, it was found that they can also be a potentially useful in nonlinear optical devices [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of the methyl derivatives of 4-nitropyridine N-oxide was described previously [14][15][16][17]. Both the perchlorates of the 4-nitropyridine N-oxides and auxiliary materials for potentiometric measurements were prepared and purified as described in papers [14][15][16][17] and references therein.…”
Section: Methodsmentioning
confidence: 99%
“…Both the perchlorates of the 4-nitropyridine N-oxides and auxiliary materials for potentiometric measurements were prepared and purified as described in papers [14][15][16][17] and references therein. Also the procedures used for purification of acetone and acetonitrile as well as the equipment used for potentiometric titrations were described in these papers [14][15][16][17].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation